Explaining disparities in BMI trajectories among older adults: a test of the double jeopardy and intersectionality hypotheses. (1st April 2020) - Liew, Hui
Abstract : This study aims to assess how heterogeneity in BMI trajectories differs across birth cohorts, race/ethnicity, gender and the level of education in the United States of America. Specifically, it seeks to examine whether the combined effects of race/ethnicity, sex and education on the differences in the BMI trajectories reflect the processes associated with double jeopardy and/or intersectionality. The empirical work of this study is based on the 1992–2014 Health and Retirement Study (HRS). Findings from growth curve modelling provide partial support for the intersectionality hypotheses. Findings revealed that different dimensions of inequality (such as race/ethnicity, sex and education) interact and intersect with one another to influence longitudinal change in BMI. Health programmes to reduce, prevent, delay or reverse the progression of obesity among the elderly should pay particular attention to Black people, females and females from racial/minority groups (Black, Hispanic, Other).